Bamboo rising: Thousands of bamboo and adobe shelters are providing relief in flood-prone regions of Pakistan, yet government bodies remain sceptical of the materials. - Ahmed, Noman (Architectural Review, 2023)
The article reviews the use of bamboo shelters in flood-prone regions of Pakistan, a joint initiative by various government bodies of Pakistan in constructing prefabricated emergency shelters based on a design by architect Yasmeen Lari, now a permanent housing solution for communities in Sindh.